The carbon fertilization effect over a century of anthropogenic CO 2 emissions: higher intracellular CO 2 and more drought resistance among invasive and native grass species contrasts with increased water use efficiency for woody plants in the US Southwest - Brandon L. Drake; David T. Hanson; Timothy K. Lowrey; Zachary D. Sharp (Global Change Biology, 2017)
From 1890 to 2015, anthropogenic carbon dioxide emissions have increased atmospheric CO 2 concentrations from 270 to 400 mol mol −1 . The effect of increased carbon emissions on plant growth and reproduction has been the subject of study of free‐air CO 2 enrichment ( FACE ) experiments. These experiments have found (i) an increase in internal CO 2 partial pressure ( c i ) alongside acclimation of photosynthetic capacity, (ii) variable decreases in stomatal conductance, and (iii) that increases in yield do not increase commensurate with CO 2 concentrations. Our data set, which includes a 115‐year‐long selection of grasses collected in New Mexico since 1892, is consistent with an increased c i as a response to historical CO 2 increase in the atmosphere, with invasive species showing the largest increase. Comparison with Palmer Drought Sensitivity Index ( PDSI ) for New Mexico indicates a moderate correlation with Δ 13 C ( r 2 = 0.32, P r 2 = 0.00, P = 0.91) after 1950. These results indicate that increased c i may have conferred some drought resistance to these grasses through increased availability of CO 2 in the event of reduced stomatal conductance in response to short‐term water shortage. Comparison with C 3 trees from arid environments ( Pinus longaeva and Pinus edulis in the US Southwest) as well as from wetter environments ( Bromus and Poa grasses in New Mexico) suggests differing responses based on environment; arid environments in New Mexico see increased intrinsic water use efficiency ( WUE ) in response to historic elevated CO 2 while wetter environments see increased c i . This study suggests that (i) the observed increases in c i in FACE experiments are consistent with historical CO 2 increases and (ii) the CO 2 increase influences plant sensitivity to water shortage, through either increased WUE or c i in arid and wet environments, respectively.